Effect of a biopesticide on the predatory activity of Delphastus pusillus (Coleoptera: Coccinellidae) - PÉREZ, RICARDO; GARCÍA-GONZÁLEZ, JAVIER; COTES, ALBA MARINA (Revista Colombiana de Entomología, 2008)
One of the aspects to consider in the development of a biopesticide is the determination of its compatibility with other control agents within an integrated pest management strategy. The effect of a biopesticide based on the fungus Lecanicillim lecanii, developed for the control of the whitefly Trialeurodes vaporariorum, on the predatory activity of Delphastus pusillus was determined. In a first experiment, the consumption of nymphs by the predator previously treated with the biopesticide was determined at 0, 24, 48, 72 and 96 hours after application of the product. In a second experiment, the consumption preference by the predator for prey that were healthy or infected with L. lecanii was determined. The consumption of nymphs decreased with the increase in time after prey infection. The greatest consumption was observed in the control treatment (healthy prey) with 64.1%, while with infected prey at 0, 24, 48, 72 and 96 hours the consumption was 39.6, 10.3, 11.4, 19.6 and 4.3% respectively. The predator showed a preference for healthy prey with a consumption of 41%, in comparison to 2.3% consumption of infected prey. The results suggest that although the biopesticide can have an indirect effect on the predator, the combination of the two biological control agents could be compatible.